Analysing Productivity and Capital Market Performance in Nigeria - Jeremiah O. EJEMEYOVWI; Victoria I. OKAFOR; Ifeoluwa I. Ogunrinola; Barnabas Amu; E. K. Bowale (Communications of International Proceedings, 2020)
To achieve planned levels of sustainable growth and development, authors in literature have argued that a nation would require a lot of investment, and the capital market is one of the verified channels through which this could be made possible. This study examines the nexus between capital market performance and productivity in Nigeria using secondary time series data from 1981 – 2018. The Johansen co integration and Granger causality tests were employed to test the hypothesis of a long run relationship and direction of causality respectively. The study finds that capital market performance positively affects economic growth in the long run, while the causality result shows the existence of a unidirectional relationship running from capital market performance to economic growth. More specifically, a 1 percent increase in capital market investment will lead to a 5.9 percent increase in productivity in Nigeria. This was corroborated by the Granger causality result. The study concludes that capital market performance plays a major role in ensuring economic growth.
Keywords: Capital Market Performance; Economic Growth; Market Capitalization; Capital Formation.